Universiti autonomy as social practice. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2009)
In Malaysia, the connection between educational reform and the values of Malaysian society needs articulation. Debates over university autonomy and globalisation are usually articulated within a frame of reference caught between two polarities: the market and the state. Universities themselves are deemed to lie between these two spheres.